2013
DOI: 10.1086/671724
|View full text |Cite
|
Sign up to set email alerts
|

Incidence Trends in Pathogen-Specific Central Line–Associated Bloodstream Infections in US Intensive Care Units, 1990–2010

Abstract: Patterns of ICU CLABSI incidence density rates among major pathogen groups have changed considerably during recent decades. CLABSI incidence declined steeply since 2006, except for CLABSI due to S. aureus in pediatric ICUs. There is a need to better understand CLABSIs that still do occur, on the basis of microbiological and patient characteristics. New prevention approaches may be needed in addition to central line insertion and maintenance practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(40 citation statements)
references
References 19 publications
(18 reference statements)
1
34
0
5
Order By: Relevance
“…Indeed, Fagan et al [12] measured incidence trends in pathogen-specific CLABSI in US ICUs from 1990 to 2010, showing a decline since 2006, with the exception of infections due to S. aureus in pediatric ICUs, probably as a consequence of surveillance programs [13]. Dreesen et al [14] evaluated differences between cancer patients and those with other conditions.…”
Section: Incidence Of Clabsi and Clinical Outcomementioning
confidence: 99%
“…Indeed, Fagan et al [12] measured incidence trends in pathogen-specific CLABSI in US ICUs from 1990 to 2010, showing a decline since 2006, with the exception of infections due to S. aureus in pediatric ICUs, probably as a consequence of surveillance programs [13]. Dreesen et al [14] evaluated differences between cancer patients and those with other conditions.…”
Section: Incidence Of Clabsi and Clinical Outcomementioning
confidence: 99%
“…In the United States, coagulase-negative staphylococci, S aureus, and Enterococcus faecalis have been identified as the most frequent causes of CLABSI. 22,23 In contrast, S aureus, other Staphylococcus spp, and Candida spp have been the most frequently identified pathogens in Chinese ICUs, 24 with Klebsiella spp, Pseudomonas spp, and Candida spp the most frequent pathogens in Indian ICUs. 25 CNS were reported as the most commonly identified cause of CLABSI in a singlecenter Brazilian study.…”
Section: Discussionmentioning
confidence: 99%
“…1,14,20 Recently, the reported number of cases of Candida spp resistant to antifungal agents has been increasing. 21 Wisplinghoff et al 22 conducted a nationwide study in the United States and reported for their concurrent surveillance study that 87% of nosocomial bloodstream infections were monomicrobial and that the most common microorganisms were coagulase-negative staphylococci (31% of isolates), S aureus (20%), enterococci (9%), and Candida spp (9%). They also reported that the mean interval between catheter insertion and infection occurrence was 16 days for S aureus and 22 days for Candida spp.…”
Section: Discussionmentioning
confidence: 99%